ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP PERSEDIAAN PT. BUANA HIJAU ABADI 2 - B51109023, DIAN SARI Br GINTING (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
Then target of this research is to knowing and analyze the system of internal control in inventory at PT Buana Hijau Abadi 2 is effective or not. The research at PT Buana Hijau Abadi 2 is have 15 Staff who directly work in inventory division. Analyzing tools which is used to record the system of internal control basically is from structure organization , flowchart analyze, internal control questionnaire and compliance test, but the result of the research is different. The result is supported by some theory, can assumed is the system of internal control at PT Buana Hijau Abadi 2 on 2012 is ineffective Keywords : Inventory, System of internal control, affectivity